The effect of variation of tetrahydropentagamavunon-0 concentration in lotion and emulgel formula toward acute dermal irritation study - Ritmaleni; Dina Suci Susilo Putri; Tia Wulandari; Abdul Karim Zulkarnain; Mimiek Murrukmihadi (Wolters Kluwer Medknow Publications, 2021)
Tetrahydropentagamavunon-0 (THPGV-0) is a curcumin metabolite analog which known has a higher antioxidant activity than Vitamin E. This compound has been formulated in lotion as antiaging cosmetics, but the irritation effect is unknown yet. This study aims to analyze the effect of variation of THPGV-0 concentration in lotion and emulgel formula toward acute dermal irritation. The concentrations of THPGV-0 varied to 0.1%, 0.2%, and 0.4% in lotion/emulgel and tested for their physical properties such as organoleptic, homogeneity, pH, spreadability, and adhesion. Acute dermal irritation test is done in accordance with the In vivo Nonclinical Toxicity Test Guidelines by the Indonesian Food and Drug Administration (BPOM). This study showed that Primary Irritation Index (PII) value concentrations of 0.1%, 0.2%, and 0.4% THPGV-0 in lotion formula are 0.014, 0.014, and 0.028 (close to 0) and in emulgel formula are 0.08 at concentration of 0.1%, 0.33 at concentration of 0.2%, and 0.25 at concentration of 0.4%. PII of 0.1%, 0.2%, and 0.4% THPGV-0 in lotion and emulgel is included in negligible irritation response. Hence, the both of THPGV-0 formula in lotion and emulgel are considered safe to use on skin according to this study.